2009
DOI: 10.1002/hec.1452
|View full text |Cite
|
Sign up to set email alerts
|

Who pays attention in stated‐choice surveys?

Abstract: Responses of inattentive or inconsistent subjects in stated-choice (SC) surveys can lead to imprecise or biased estimates. Several SC studies have investigated inconsistency and most of these studies dropped subjects who were inconsistent. However, none of these studies reported who is more likely to fail consistency tests. We investigated the effect of the personal characteristics and task complexity on preference inconsistency in eight different SC surveys. We found that white, higher-income and better-educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…As noted previously, DCEs are challenging for participants [44], requiring motivation, literacy, and numeracy, which may introduce selection bias [23]. We attempted to reduce this effect by using an interviewer rather than a postal questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, DCEs are challenging for participants [44], requiring motivation, literacy, and numeracy, which may introduce selection bias [23]. We attempted to reduce this effect by using an interviewer rather than a postal questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the prostate cancer-screening cohort, a majority of the participants indicated that they did not understand one or more attributes (mostly the risk attributes). Studies state that a lack of understanding of certain attribute (levels) might be due to a lower educational level, older age and a lower health literacy [ 8 , 21 , 23 , 45 , 46 ]. The current study indeed showed that the number of attributes included in decision-making, decision strategy, interpretation of the risk attributes and understanding of the risk attributes differed between participants with different educational levels and health literacy scores.…”
Section: Discussionmentioning
confidence: 99%
“…The prior28 estimates of attribute coefficients used in the final efficient design were derived from a pilot survey (see below). A further three choice sets were added to each block as tests of transitivity29 30 and monotonicity29—which are tests of theoretical validity and rationality of choice sets used in the DCE. Theoretical validity and rationality checks assessed whether the parameters moved in the expected direction.…”
Section: Methodsmentioning
confidence: 99%